1991
DOI: 10.1126/science.253.5022.866
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Conservation of Plant Genetic Resources: Global Development and Environmental Concerns

Abstract: Conservation of plant genetic resources is achieved by protection of populations in nature (in situ) or by preservation of samples in gene banks (ex situ). The latter are essential for users of germplasm who need ready access. Ex situ conservation also acts as a back-up for certain segments of diversity that might otherwise be lost in nature and in human-dominated ecosystems. The two methods are complementary, yet better understanding of this interrelation and the role of ex situ conservation in global environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
9

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 11 publications
0
44
0
9
Order By: Relevance
“…Although the need to address this challenge has been recognized for many years now (e.g. Ledig 1988;Cohen et al 1991;Yang and Yeh 1992;Etisham-Ul-Haq et al 2001), no significant improvements have been made in the last decades (Ensslin et al 2011;Rucinska and Puchalski 2011). Namoff et al (2010) proposed to collect at least 15 plants preferably from 3 accessions for purposes of maintaining genetic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the need to address this challenge has been recognized for many years now (e.g. Ledig 1988;Cohen et al 1991;Yang and Yeh 1992;Etisham-Ul-Haq et al 2001), no significant improvements have been made in the last decades (Ensslin et al 2011;Rucinska and Puchalski 2011). Namoff et al (2010) proposed to collect at least 15 plants preferably from 3 accessions for purposes of maintaining genetic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…La conservación in situ, permite que las poblaciones se desarrollen y se relacionen dentro de sus hábitats naturales. Sin embargo, en el mundo real y en la práctica, los dos métodos son necesarios dado que la conservación ex situ actúa como respaldo para ciertos segmentos de la diversidad que podrían desaparecer en la naturaleza y en los ecosistemas dominados por la humanidad (Cohen et al, 1991;Wyse Jackson y Sutherland, 2000). Los jardines botánicos son quizás las únicas instituciones que cuentan con infraestructura y personal especializado con la experiencia en taxonomía, horticultura y especialmente, adaptados para el manejo de especies vivas en colecciones que jamás han sido cultivadas ni domesticadas.…”
Section: Los Jardines Botánicos Y La Crisis De La Biodiversidadunclassified
“…A nivel mundial se reconoce la importancia de conservar las variedades antiguas de plantas no comerciales y los parientes silvestres de los cultivos para el fi tomejoramiento, la resistencia a plagas y condiciones ambientales adversas (Heslop-Harrison, 1974;Cohen et al, 1991). Por ejemplo, existen 7,500 variedades de manzanas (Malus domestica L.) a nivel mundial (University of Illinois); sin embargo, en los supermercados únicamente están disponibles unas cuantas.…”
Section: Conservación De Variedades En Desusounclassified
“…Cohen et al (1991) found the performance of IRRI and CIMMYT (International Maize and Wheat Improvement Center) to be exemplary, having 90 per cent of accessions sucient for distribution, and the performance of the other IARC centres was apparently good relative to most other germplasm facilities.…”
Section: Current Ex Situ Facilities and Their Managementmentioning
confidence: 99%